The Effectiveness of Strength-Based Intervention on Attitude Toward Marital Infidelity and Sexual Self-Concept in Women with Marital Conflict - Ghadaki, Maryam; Darbani, Seyed Ali (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to evaluate the effectiveness of a strength-based intervention on altering attitudes toward marital infidelity and enhancing sexual self-concept among women experiencing marital conflict. Methods: A randomized controlled trial design was employed with 30 women from the Mehravar Counseling Center in Tehran, divided equally into intervention and control groups. The intervention consisted of eight 75-minute sessions based on strength-based principles. Data were collected at three points using the Attitudes Towards Infidelity Scale (ATIS) and the Sexual Self-Concept Inventory (SSCI). Statistical analysis was conducted using ANOVA with repeated measurements and Bonferroni post-hoc tests, utilizing SPSS-27. Findings: The intervention group showed significant improvements in both measured outcomes. Attitudes toward marital infidelity decreased from a pre-test mean of 42.53 (SD = 5.67) to 37.82 (SD = 5.12) at follow-up. Sexual self-concept increased from a pre-test mean of 30.88 (SD = 4.45) to 35.64 (SD = 3.72) at follow-up. The ANOVA results revealed significant time effects and time x group interactions for both variables (p < .001). Conclusion: The strength-based intervention was effective in significantly improving attitudes toward marital infidelity and sexual self-concept among women with marital conflicts. These findings suggest that such interventions can be beneficial in marital counseling settings, offering a promising approach for enhancing marital satisfaction and individual well-being.